2023
DOI: 10.5765/jkacap.220041
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Mental Health in Children and Adolescents During the COVID-19 Pandemic

Abstract: This paper reviews the global effect of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of children and adolescents in South Korea, the U.S., Japan, and China. We reviewed research on deteriorated mental health, including increased suicide, suicidal thoughts, and self-harm. Various studies have shown that students' mental health issues, such as depression and anxiety, have worsened during the COVID-19 pandemic. Furthermore, the number of students who committed suicide has significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a survey conducted in the Yellowstone area of America found that the year 2021, the year of the COVID-19 epidemic, saw a marked increase in the incidence of depression among adolescents [40] . Suicide is a fatal outcome for people with depression and depression has worsened adolescent mental health and increased suicide rates globally since the pandemic [41] . A large case-control study in China con rmed that depression, particularly depression severity scores in the two weeks before death, are important predictors of suicide [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a survey conducted in the Yellowstone area of America found that the year 2021, the year of the COVID-19 epidemic, saw a marked increase in the incidence of depression among adolescents [40] . Suicide is a fatal outcome for people with depression and depression has worsened adolescent mental health and increased suicide rates globally since the pandemic [41] . A large case-control study in China con rmed that depression, particularly depression severity scores in the two weeks before death, are important predictors of suicide [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety symptoms are the most frequent mental health problems among adolescents and are significant risk factors for suicide ( 71 , 72 ). Among adolescents, depression, anxiety and other mental health problems may have worsened during the pandemic, increasing the prevalence of suicide ( 73 ). Our work highlights that prevalence of suicidal ideation and suicide attempts remains relatively high among young people even after the lifting of COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The increased learning burden and reduced number of close friendships can cause depression and anxiety in adolescents. Moreover, restrictions on access to mental health services due to social distancing can also contribute to worsening depression and anxiety [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%